Adequacy of Evidence for Physical Activity Guidelines Development: Workshop Summary - Institute of Medicine
Is there a sufficient evidence base for the U.S. Department of Health and Human Services (HHS) to develop a comprehensive set of physical activity guidelines for Americans? To address this question, the Institute of Medicine (IOM) held a workshop titled \

Advancing Nuclear Medicine Through Innovation - Institute of Medicine; National Research Council (The National Academies Press, 2007)
Nearly 20 million nuclear medicine procedures are carried out each year in the United States alone to diagnose and treat cancers, cardiovascular disease, and certain neurological disorders. Many of the advancements in nuclear medicine have been the result of research investments made during the past 50 years where these procedures are now a routine part of clinical care. Although nuclear medicine plays an important role in biomedical research and disease management, its promise is only beginning to be realized. Advancing Nuclear Medicine Through Innovation highlights the exciting emerging opportunities in nuclear medicine, which include assessing the efficacy of new drugs in development, individualizing treatment to the patient, and understanding the biology of human diseases. Health care and pharmaceutical professionals will be most interested in this book's examination of the challenges the field faces and its recommendations for ways to reduce these impediments.

Mobilizing Science-Based Enterprises for Energy, Water, and Medicines in Nigeria - National Research Council (The National Academies Press, 2007)

Progress in Preventing Childhood Obesity: How Do We Measure Up? - Institute of Medicine (The National Academies Press, 2007)
The remarkable increase in the prevalence of obesity among children and youth in the United States over a relatively short timespan represents one of the defining public health challenges of the 21st century. The country is beginning to recognize childhood obesity as a major public health epidemic that will incur substantial costs to the nation. However, the current level of investment by the public and private sectors still does not match the extent of the problem. There is a substantial underinvestment of resources to adequately address the scope of this obesity crisis. At this early phase in addressing the epidemic, actions have begun on a number of levels to improve the dietary patterns and to increase the physical activity levels of young people. Schools, corporations, youth-related organizations, families, communities, foundations, and government agencies are working to implement a variety of policy changes, new programs, and other interventions. These efforts, however, generally remain fragmented and small in scale. Moreover, the lack of systematic monitoring and evaluation of interventions have hindered the development of an evidence base to identify, apply, and disseminate lessons learned and to support promising efforts to prevent childhood obesity. Progress in Preventing Childhood Obesity: How Do We Measure Up? examines the progress made by obesity prevention initiatives in the United States from 2004 to 2006. This book emphasizes a call to action for key stakeholders and sectors to commit to and demonstrate leadership in childhood obesity prevention, evaluates all policies and programs, monitors their progress, and encourages stakeholders to widely disseminate promising practices. This book will be of interest to federal, state, and local government agencies; educators and schools; public health and health care professionals; private-sector companies and industry trade groups; media; parents; and those involved in implementing community-based programs and consumer advocacy.

Assessing the Medical Risks of Human Oocyte Donation for Stem Cell Research: Workshop Report - Institute of Medicine; National Research Council (The National Academies Press, 2007)
It is widely understood that stem cell treatments have the potential to revolutionize medicine. Because of this potential, in 2004 California voters approved Proposition 71 to set up a 10-year, 3 billion program to fund research on stem cells. Under the direction of the California Institute for Regenerative Medicine, this program will pay to build facilities for stem cell research and will fund doctors and scientists to carry out research with the ultimate goal of helping to develop therapies based on stem cells. For this research to move forward, however, will require a steady supply of stem cells, particularly human embryonic stem cells. Those stem cells are collected from developing human embryos created from eggs2014or oocytes2014harvested from the ovaries of female donors. Thus much of the promise of stem cells depends on women choosing to donate oocytes to the research effort. The oocyte donation process is not without risk, however. Donors are given doses of hormones to trigger the production of more eggs than would normally be produced, and this hormone treatment can have various side effects. Once the eggs have matured in the ovary, they must be retrieved via a surgical procedure that is typically performed under anesthesia, and both the surgery and the anesthesia carry their own risks. Furthermore, given the very personal nature of egg donation, the experience may carry psychological risks for some women as well. With this in mind, in 2006 the California Institute for Regenerative Medicine contracted with the National Academies to organize a workshop that would bring together experts from various areas to speak about the potential risks of oocyte donation and to summarize what is known and what needs to be known about this topic. The Committee on Assessing the Medical Risks of Human Oocyte Donation for Stem Cell Research was formed to plan the workshop, which was held in San Francisco on September 28, 2006. This report is a summary and synthesis of that workshop.

Opportunities for Coordination and Clarity to Advance the National Health Information Agenda: A Brief Assessment of the Office of the National Coordinator for Health Information Technology: A Letter Report - Institute of Medicine; National Research Council (The National Academies Press, 2007)

Cancer Biomarkers: The Promises and Challenges of Improving Detection and Treatment - Institute of Medicine (The National Academies Press, 2007)
Many cancer patients are diagnosed at a stage in which the cancer is too far advanced to be cured, and most cancer treatments are effective in only a minority of patients undergoing therapy. Thus, there is tremendous opportunity to improve the outcome for people with cancer by enhancing detection and treatment approaches. Biomarkers will be instrumental in making that transition. Advances in biotechnology and genomics have given scientists new hope that biomarkers can be used to improve cancer screening and detection, to improve the drug development process, and to enhance the effectiveness and safety of cancer care by allowing physicians to tailor treatment for individual patients&#8212an approach known as personalized medicine. However, progress overall has been slow, despite considerable effort and investment, and there are still many challenges and obstacles to overcome before this paradigm shift in oncology can become a reality.

Gulf War and Health: Volume 5: Infectious Diseases - Institute of Medicine (The National Academies Press, 2007)
Infectious diseases have been a problem for military personnel throughout history. The consequences in previous conflicts have ranged from frequent illnesses disrupting daily activities and readiness to widespread deaths. Preventive measures, early diagnosis, and treatment greatly limit the exposures and acute illnesses of troops today in comparison with those in armies of the past, but infections and consequent acute illnesses still occur. Thousands of US veterans of the Persian Gulf War have reported an array of unexplained illnesses since the war ended in 1991. Many veterans have believed that the illnesses were associated with their military service in southwest Asia during the war. This volume of Gulf War and Health evaluates the scientific literature on chemical, biologic, and physical agents to which military personnel in the gulf were potentially exposed and possible long-term adverse health outcomes.

Green Schools: Attributes for Health and Learning - National Research Council (The National Academies Press, 2007)
Evidence has accumulated that shows that the quality of indoor environments can affect the health and productivity of adults and children. One consequence is that a movement has emerged to promote the design of schools that have fewer adverse environmental effects. To examine the potential of such design for improving education, several private organizations asked the NRC to review and assess the health and productivity benefits of green schools. This report provides an analysis of the complexity of making such a determination; and an assessment of the potential human health and performance benefits of improvements in the building envelope, indoor air quality, lighting, and acoustical quality. The report also presents an assessment of the overall building condition and student achievement, and offers an analysis of and recommendations for planning and maintaining green schools including research considerations.

Long-Term Health Effects of Participation in Project SHAD (Shipboard Hazard and Defense) - Institute of Medicine (The National Academies Press, 2007)
More than 5,800 military personnel, mostly Navy personnel and Marines, participated in a series of tests of U.S. warship vulnerability to biological and chemical warfare agents, Project SHAD (Shipboard Hazard and Defense), in the period 1962-1973. Only some of the involved military personnel were aware of these tests at the time. Many of these tests used simulants, substances with the physical properties of a chemical or biological warfare agent, thought at the time to have been harmless. The existence of these tests did not come to light until many decades later. In September 2002, the Institute of Medicine (IOM) agreed to undertake a scientific study, funded by the Veterans' Affairs, of potential long-term health effects of participation in Project SHAD. In general, there was no difference in all-cause mortality between Project SHAD participants and nonparticipant controls, although participants statistically had a significantly higher risk of death due to heart disease, had higher levels of neurodegenerative medical conditions and higher rates of symptoms with no medical basis. Long-Term Health Effects of Participation in Project SHAD focuses on the potential health effects of participation in Project SHAD. It is a useful resource for government defense agencies, scientists and health professionals.

Implementing Cancer Survivorship Care Planning: Workshop Summary - Institute of Medicine
One of the key recommendations of the joint IOM and NRC book, From Cancer Patient to Cancer Survivor: Lost in Transition, is that patients completing their primary treatment for cancer be given a summary of their treatment and a comprehensive plan for follow-up. This book answers practical questions about how this \

Cancer Control Opportunities in Low- and Middle-Income Countries - Institute of Medicine (The National Academies Press, 2007)
Cancer is low or absent on the health agendas of low- and middle-income countries (LMCs) despite the fact that more people die from cancer in these countries than from AIDS and malaria combined. International health organizations, bilateral aid agencies, and major foundations&#8212which are instrumental in setting health priorities&#8212also have largely ignored cancer in these countries. This book identifies feasible, affordable steps for LMCs and their international partners to begin to reduce the cancer burden for current and future generations. Stemming the growth of cigarette smoking tops the list to prevent cancer and all the other major chronic diseases. Other priorities include infant vaccination against the hepatitis B virus to prevent liver cancers and vaccination to prevent cervical cancer. Developing and increasing capacity for cancer screening and treatment of highly curable cancers (including most childhood malignancies) can be accomplished using &#34resource-level appropriateness&#34 as a guide. And there are ways to make inexpensive oral morphine available to ease the pain of the many who will still die from cancer.

Preventing Medication Errors - Institute of Medicine (The National Academies Press, 2007)
In 1996 the Institute of Medicine launched the Quality Chasm Series, a series of reports focused on assessing and improving the nation's quality of health care. Preventing Medication Errors is the newest volume in the series. Responding to the key messages in earlier volumes of the series2014To Err Is Human (2000), Crossing the Quality Chasm (2001), and Patient Safety (2004)2014this book sets forth an agenda for improving the safety of medication use. It begins by providing an overview of the system for drug development, regulation, distribution, and use. Preventing Medication Errors also examines the peer-reviewed literature on the incidence and the cost of medication errors and the effectiveness of error prevention strategies. Presenting data that will foster the reduction of medication errors, the book provides action agendas detailing the measures needed to improve the safety of medication use in both the short- and long-term. Patients, primary health care providers, health care organizations, purchasers of group health care, legislators, and those affiliated with providing medications and medication- related products and services will benefit from this guide to reducing medication errors.

The Learning Healthcare System: Workshop Summary - Institute of Medicine (The National Academies Press, 2007)
As our nation enters a new era of medical science that offers the real prospect of personalized health care, we will be confronted by an increasingly complex array of health care options and decisions. The Learning Healthcare System considers how health care is structured to develop and to apply evidence–from health profession training and infrastructure development to advances in research methodology, patient engagement, payment schemes, and measurement–and highlights opportunities for the creation of a sustainable learning health care system that gets the right care to people when they need it and then captures the results for improvement. This book will be of primary interest to hospital and insurance industry administrators, health care providers, those who train and educate health workers, researchers, and policymakers. The Learning Healthcare System is the first in a series that will focus on issues important to improving the development and application of evidence in health care decision making. The Roundtable on Evidence-Based Medicine serves as a neutral venue for cooperative work among key stakeholders on several dimensions: to help transform the availability and use of the best evidence for the collaborative health care choices of each patient and provider; to drive the process of discovery as a natural outgrowth of patient care; and, ultimately, to ensure innovation, quality, safety, and value in health care.

Smart Prosthetics: Exploring Assistive Devices for the Body and Mind: Task Group Summaries (The National Academies Press, 2007)
The 2006 conference, 201cSmart Prosthetics: Exploring Assistive Devices for the Body and Mind,201d attracted scientists, engineers and medical researchers to participate in a series of task groups to develop research plans to address various challenges within the prosthetics field. Eleven conference task groups gave the participants eight hours to develop new research approaches to various challenges, including: build a smart prosthesis that will grow with a child; develop a smart prosthetic that can learn better and\/or faster; refine technologies to create active orthotic devices; and describe a framework for replacing damaged cortical tissue and fostering circuit integration to restore neurological function. Representatives from public and private funding organizations, government, industry, and the science media also participated in the task groups. This book provides a summary of the conference task groups. For more information about the conference, visit the Smart Prosthetics conference site. The National Academies Keck Futures Initiative was launched in 2003 to stimulate new modes of scientific inquiry and break down the conceptual and institutional barriers to interdisciplinary research. The National Academies and the W.M. Keck Foundation believe considerable scientific progress and social benefit will be achieved by providing a counterbalance to the tendency to isolate research within academic fields. The Futures Initiative is designed to enable researchers from different disciplines to focus on new questions upon which they can base entirely new research, and to encourage better communication between scientists as well as between the scientific community and the public. Funded by a 40 million grant from the W.M. Keck Foundation, the National Academies Keck Futures Initiative is a 15-year effort to catalyze interdisciplinary inquiry and to enhance communication among researchers, funding agencies, universities, and the general public with the object of stimulating interdisciplinary research at the most exciting frontiers. The Futures Initiative builds on three pillars of vital and sustained research: interdisciplinary encounters that counterbalance specialization and isolation; the identification and exploration of new research topics; and communication that bridges languages, cultures, habits of thought, and institutions. Toward these goals, the National Academies Keck Futures Initiative incorporates three core activities each year: Futures conferences, Futures grants, and National Academies Communication Awards. For more information about the Initiative, visit www.keckfutures.org.

The Future of Disability in America - Institute of Medicine (The National Academies Press, 2007)
The future of disability in America will depend on how well the U.S. prepares for and manages the demographic, fiscal, and technological developments that will unfold during the next two to three decades. Building upon two prior studies from the Institute of Medicine (the 1991 Institute of Medicine's report Disability in America and the 1997 report Enabling America), The Future of Disability in America examines both progress and concerns about continuing barriers that limit the independence, productivity, and participation in community life of people with disabilities. This book offers a comprehensive look at a wide range of issues, including the prevalence of disability across the lifespan; disability trends the role of assistive technology; barriers posed by health care and other facilities with inaccessible buildings, equipment, and information formats; the needs of young people moving from pediatric to adult health care and of adults experiencing premature aging and secondary health problems; selected issues in health care financing (e.g., risk adjusting payments to health plans, coverage of assistive technology); and the organizing and financing of disability-related research. The Future of Disability in America is an assessment of both principles and scientific evidence for disability policies and services. This book's recommendations propose steps to eliminate barriers and strengthen the evidence base for future public and private actions to reduce the impact of disability on individuals, families, and society.

Preterm Birth: Causes, Consequences, and Prevention - Institute of Medicine (The National Academies Press, 2007)
The increasing prevalence of preterm birth in the United States is a complex public health problem that requires multifaceted solutions. Preterm birth is a cluster of problems with a set of overlapping factors of influence. Its causes may include individual-level behavioral and psychosocial factors, sociodemographic and neighborhood characteristics, environmental exposure, medical conditions, infertility treatments, and biological factors. Many of these factors co-occur, particularly in those who are socioeconomically disadvantaged or who are members of racial and ethnic minority groups. While advances in perinatal and neonatal care have improved survival for preterm infants, those infants who do survive have a greater risk than infants born at term for developmental disabilities, health problems, and poor growth. The birth of a preterm infant can also bring considerable emotional and economic costs to families and have implications for public-sector services, such as health insurance, educational, and other social support systems. Preterm Birth assesses the problem with respect to both its causes and outcomes. This book addresses the need for research involving clinical, basic, behavioral, and social science disciplines. By defining and addressing the health and economic consequences of premature birth, this book will be of particular interest to health care professionals, public health officials, policy makers, professional associations and clinical, basic, behavioral, and social science researchers.

The Future of Drug Safety: Promoting and Protecting the Health of the Public - Institute of Medicine (The National Academies Press, 2007)
In the wake of publicity and congressional attention to drug safety issues, the Food and Drug Administration (FDA) requested the Institute of Medicine assess the drug safety system. The committee reported that a lack of clear regulatory authority, chronic underfunding, organizational problems, and a scarcity of post-approval data about drugs&#39 risks and benefits have hampered the FDA&#39s ability to evaluate and address the safety of prescription drugs after they have reached the market. Noting that resources and therefore efforts to monitor medications&#39 risk2013benefit profiles taper off after approval, The Future of Drug Safety offers a broad set of recommendations to ensure that consideration of safety extends from before product approval through the entire time the product is marketed and used.

Challenges in Adolescent Health Care: Workshop Report - National Research Council; Institute of Medicine (The National Academies Press, 2007)
Several positive and negative lifelong behaviors are established during adolescence including diet and exercise, sexual conduct, practices related to oral health, smoking, drinking, and the use if legal and illegal substances. The complex issues that adolescents deal with on a daily basis can turn into health problems that persist throughout adulthood. Unfortunately the adolescents who are frequently the most disconnected from routine health care services - those who lack insurance and family support - are often those at greatest risk for multiple and chronic health problems. Therefore, those that are responsible for delivering health care services to adolescents must address the health conditions that require immediate attention while preparing young people to adopt practices that can help improve their future health status and prevent unhealthy behaviors. Challenges in Adolescent Health Care studies adolescent health care in the United States, highlights critical health care needs, and identifies service models and components of care that may strengthen and improve health care services, settings, and systems for adolescents. The book explores the nature of adolescent challenges and how they reflect larger societal issues such as poverty, crime and the prevalence of violence. These issues, in addition to lack of comprehensive health coverage, dysfunctional families and the lack of support systems, make providing adequate health care incredibly challenging. Challenges in Adolescent Health Care defines high-quality health care, identifies the strengths and weaknesses of various service models and explores various training programs. The book recommends that health care providers must be sensitive to socioeconomic factors and incorporate health care in a broad array of settings including schools, neighborhoods and community centers.

The State of Quality Improvement and Implementation Research: Expert Views: Workshop Summary - Institute of Medicine
The Institute of Medicine (IOM) workshop \